Pengaruh Konservatisme Akuntansi, Kepemilikan Manajerial, dan Dewan Komisaris Independen Terhadap Penghindaran Pajak - Heriyanto Saputra; Anita Kusuma Dewi; Eksa Ridwansyah (Al-Muhasabah: Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
Tax avoidance is a way to reduce the tax burden that is justified by tax law. Tax avoidance can be measured using the Cash Effective Tax Rate (CETR). This study aims to determine the effect of accounting conservatism, managerial ownership, and independent board of commissioners on tax avoidance in property and real estate companies listed on the IDX for the period 2018-2021. Sample determination using purposive sampling method. The number of samples selected was 9 companies with a research period of 4 years so that a total of 36 data was obtained and after eliminating outlier data, there were 32 samples. The data used is quantitative data with data collection methods in the form of documentation methods. Data analysis using multiple linear regression analysis. The results of the study indicate that accounting conservatism and independent board of commissioners have no effect on tax avoidance, while managerial ownership affects tax avoidance.